MENINGKATKAN KOMPETENSI GURU DALAM PERANCANGAN PEMBELAJARAN BERBASIS KURIKULUM PEMBELAJARAN MENDALAM - Agus Wedi; I Nyoman Sudana Degeng; Deka Dyah Utami; Otto Fajarianto; Arafah Husna; Yulias Prihatmoko; Nugroho, Rengga Prakoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This community service activity aims to enhance the competence of elementary school teachers in designing and implementing Project-Based Learning (PjBL) and Case Method instruction using a deep learning approach. The activity was motivated by the challenges teachers face in adopting the Merdeka Curriculum, particularly the limited conceptual understanding and skills in designing innovative learning experiences. The program was conducted at SDN 03 Mulyorejo, Malang City, involving 20 teachers as participants. The implementation methods included material delivery, hands-on practice, and evaluation using pre- and post-training instruments based on Kirkpatrick’s evaluation framework at the learning level. The results indicated a significant improvement in teachers’ understanding of deep learning concepts and their self-efficacy in designing project- and case-based learning. All participants (100%) reported the ability to adapt deep learning in the context of the Merdeka Curriculum and integrate information technology into the learning process. In addition, the development of a Digital Learning Resource Center served as ongoing support for teachers to independently apply deep learning practices. These outcomes reinforce previous findings that practice-based training, reflection, and technology integration play a crucial role in enhancing teacher professionalism and learning quality. This activity is recommended for replication in other elementary schools to expand the implementation of deep learning as part of the Merdeka Curriculum strategy.